Synthesis, Molecular docking and Biological evaluation of 4-Cycloalkylidineamino 1, 2-Naphthoquinone Semicarbazones as Anticancer agents - Shukla S.; Srivastava R.S.; Shrivastava S.K.; Sodhi A.; Kumar P. (My University, 2025)
Objective: In an effort to etablish new candidates with improved antineoplastic activity, 4-cycloalkylidineamino 1,2-naphthoquinone semicarbazones were synthesized, characterized and evaluated for anticancer activity. Method: The desired compounds were synthesized by condensation of 4- amino1, 2-naphthoquinone with cyclic ketones and further subsequent reaction of this product with semicarbazide hydrochloride. Compounds were characterized by FT-IR, 1H NMR, 13C NMR, elemental analysis and screened for antiproliferative activity against three human cancer cell lines (HepG2, MG-63 and MCF-7) by MTT assay using doxorubicin as standard. Docking was performed by using the Glide 5.7 integrated with Maestro 9.2 (Schrödinger, LLC, 2011) to understand the binding preference of synthesized compounds with target enzyme topoisomerase-II. Results: 4-(cyclohexylideneamino) [1, 2] naphthoquinone 2-semicarbazone was found to be most active cytotoxic agent against all cancer cell lines with IC50 values in the range of 5.58-6.31 μM. Results of molecular docking were also well correlated in vitro cytotoxicity assay. Insilico ADME studies revealed the drug likeliness of compounds. Conclusions: The synthesized compounds were found to have significant anticancer activity and able to enter in higher phases of the drug development process due to favorable pharmacokinetic properties. © 2012 Asian Pacific Tropical Biomedical Magazine.